Materialismo e suas influências na qualidade de vida subjetiva dos adolescentes da cidade de João Pessoa/PB. - Nascimento, Janine Silva do (2016)
This dissertation addresses three main issues: materialism, Subjective Quality of Life (SQL) and adolescents. Being the teenagers considered the subjects of this research. In the field of marketing, issues such as these are being extensively studied. Materialism is considered a characteristic of the consumer field in its general aspects, which translates the identification with the possession and acquisition of material goods as a central factor in their lives, a source of happiness and success. It is also considered aspects such as possessiveness, lack of generosity and jealousy. The subjective quality of life is the perception of the individual regarding their own quality of life, treated in this study as well as life satisfaction and subjective well-being. That said the study was meant to examine the influence of materialism on the subjective quality of life of adolescents and thus identify the background of materialism in these individuals; verify their perception of subjective quality of life, as well as its relationship with the levels of materialism. In this sense, hypotheses were elaborated from the theoretical construction, the objectives and the proposed research model. To enable the implementation of empirical research, 705 questionnaires were applied in person in public and private schools in the city of João Pessoa/PB, resulting in 667 valid questionnaires, with adolescents aged from 12 to incomplete 18 years. Therefore, two scales were utilized (materialism and SQL) validated for the target public, the first from Goldberg et al. (2003) Youth Materialism Scala - YMC and the second from Patrick et al. (2002) Youth Quality of Life Instrument - YQOL. Data were analyzed using SPSS software. The results showed in a general way that adolescents from this sample showed intermediate levels of both materialism and SQL. The only antecedent of materialism confirmed by the hypotheses was the influence of the possessions of the pairs. All other antecedents: age, social class, family relationships, self-esteem were rejected. In the same way that it has not been confirmed a direct influence of materialism level with the level of subjective quality of life, the latter treated as resultant in this study.